2017
DOI: 10.1088/1742-6596/791/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Positron annihilation study of cavities in black Au films

Abstract: Abstract. Defects in a black Au film were studied using variable energy positron annihilation spectroscopy. Black Au films exhibit porous morphology similar to cauliflower. This type of structure enhances the optical absorption due to a multiple reflections in the micro-cavities. A nanostructured black Au film was compared with conventional smooth Au films with high reflectivity. The black Au film exhibited a remarkably enhanced S-parameter in sub-surface region. This is caused by a narrow para-Positronium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Generally, black metals are considered to be stable up to 300 °C. [ 5 ] Several metals, such as silver, [ 6 ] gold, [ 7,8 ] platinum, [ 9 ] tungsten, [ 10 ] titanium, [ 11 ] palladium, [ 12 ] and aluminum, [ 13,14 ] are known to be fabricated in the form of black metals. Black aluminum (Black Al) is a metal that has good thermal stability and at the same time is inexpensive to produce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, black metals are considered to be stable up to 300 °C. [ 5 ] Several metals, such as silver, [ 6 ] gold, [ 7,8 ] platinum, [ 9 ] tungsten, [ 10 ] titanium, [ 11 ] palladium, [ 12 ] and aluminum, [ 13,14 ] are known to be fabricated in the form of black metals. Black aluminum (Black Al) is a metal that has good thermal stability and at the same time is inexpensive to produce.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Such coatings must have good thermal stability, namely they must retain their porous structure and, consequently, heatabsorbing properties at elevated temperatures. Generally, black metals are considered to be stable up to 300 C. [5] Several metals, such as silver, [6] gold, [7,8] platinum, [9] tungsten, [10] titanium, [11] palladium, [12] and aluminum, [13,14] are known to be fabricated in the form of black metals. Black aluminum (Black Al) is a metal that has good thermal stability and at the same time is inexpensive to produce.…”
mentioning
confidence: 99%
“…3. The S(E) curve for a well annealed (1000 [13] is plotted in the figure as well. The S parameter values were always normalized to the bulk parameter value S 0 for the well annealed Au reference.…”
Section: Resultsmentioning
confidence: 99%
“…Use of BMs in gas sensor applications profits from their extraordinary large surface area, e.g., 60 m 2 /g for black Pd [5]. BM films of various elements are deposited usually by thermal evaporation in carefully adjusted low pressure (∼ 100 Pa) of N 2 gas [7,8]. It has been reported that BMs can be prepared also by magnetron sputtering in Ar with small amount of N 2 [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…BM films of various elements are deposited usually by thermal evaporation in carefully adjusted low pressure (∼ 100 Pa) of N 2 gas [7,8]. It has been reported that BMs can be prepared also by magnetron sputtering in Ar with small amount of N 2 [6][7][8][9][10]. In the growth of metallic films in PVD systems contamination from residual atmosphere should be considered [11].…”
Section: Introductionmentioning
confidence: 99%